Faktor - Faktor yang Berhubungan dengan Perilaku Merokok Siswa SMK Taman Harapan Bekasi Tahun 2024 - Dea Maulinda; Linda, Ony; A’yunin, Elia Nur (JURNAL PENDIDIKAN KESEHATAN, 2024)
Adolescent smoking in Indonesia is often seen among high school students because this age is a transition period between childhood and adulthood. The purpose of this study was to determine the relationship between knowledge, attitudes, facilities and infrastructure, family influence, advertising exposure, and peer influence with student smoking behavior at SMK Taman Harapan Bekasi in 2024. Methods: This study used an analytic quantitative method with a cross sectional study design. The sampling technique was simple random sampling. The population in this study were all male students with a sample size of 106 respondents. The data collection method used a questionnaire sheet. The research was conducted from April 2023 to May 2024. Data processing and data analysis using chi-square. It was found that students who had smoking behavior were 51.9%, poor knowledge was 67.9%, poor attitude was 54.7%; available facilities and infrastructure were 93.4%, family influence was 67.0%, advertising exposure was 56.6% and peer influence was 53.8%. The results of the bivariate test showed a relationship between attitude (p-value = 0.012) and exposure to advertising (p-value = 0.000) while there was no relationship between knowledge (p-value = 1.000), facilities and infrastructure (p-value = 0.258), family influence (p-value = 0.888) and peer influence (p-value = 0.977) with smoking behavior in students of SMK Taman Harapan Bekasi. Students are expected to instill an attitude of changing smoking habits and building awareness, especially in cigarette advertisements there are negative things that are likely to happen if they often see them and are more easily influenced by cigarette advertisements, participating in routine positive activities at school at least once a month needs to be done to keep control of smoking behavior in students.